MEMBACA KILAS REGULASI PEREKONOMIAN DI INDONESIA DAN MENAKAR PERAN PERBANKAN SYARIAH - Syaifuddin, Selamet (Universitas Islam Negeri Sunan Kudus, 2018)
The New Order era was a time of great economic decline. Faced with the problem, the New Order government took a strategic and pragmatic step, namely with the development of the economy oriented abroad. This orientation is intended for foreign investors to enter and invest their shares in Indonesia. This policy has had a positive impact on Indonesia's economic development with the entry of foreign investors to Indonesia, especially Japan and Europe. The declining Indonesian economy, the legacy of the Old Order can be overcome. Such an overseas-oriented development strategy is supported by the surge in oil prices in the international market or known as the oil and gas boom era in the period 1973-1982.It is no exaggeration if the factors: foreign aid and foreign exchange from oil and gas (oil and gas) are two of the most supportive factors in overcoming the Indonesian economy. These two factors contribute the most to national development funds. However, dependence on foreign aid as a source of development funds can no longer be a major backdrop in line with the world economic recession that occurred in the early 1980s. Of course, the world economic recession has had a huge impact on Indonesia's donor countries. The deteriorating economic condition of those affected by aid funds is being donated to recipient countries, including Indonesia